Analysis of 20 kV Underground Cable Network Implementation on SM3 Feeder, Tomohon Main Substation - Yehezkiel Eliezer Tangkawarouw; Sandro Welly Lendeng; Arnold Robert Rondonuwu; Nathaniel Lumalan Bijang; Donald Bastian Noya (Riviera Publishing, 2026)
The continuous growth of electricity demand requires a reliable and efficient distribution system. The SM3 Feeder at the Tomohon Main Substation (GI Tomohon), managed by PT PLN (Persero) UP3 Manado, is a critical medium-voltage distribution network serving the Tomohon city centre area. The feeder currently employs overhead aerial conductors that are vulnerable to environmental disturbances such as extreme weather, strong winds, lightning, and vegetation contact, which leads to frequent outages and reduced supply quality. This study investigates the implementation of a 20 kV underground cable network on the SM3 Feeder as a strategy to improve system reliability. The methodology encompasses field surveys, technical data collection, and comparative performance analysis of the distribution system before and after underground cable implementation. Quantitative analysis was applied to evaluate technical parameters including fault frequency, and the reliability indices SAIDI and SAIFI, while qualitative analysis is used to assess the practical advantages and constraints observed during field implementation. Results demonstrate that underground cable implementation significantly reduces environmentally induced faults, providing improvements in safety, system reliability, and urban aesthetics. Although capital investment and installation costs are considerably higher than those of overhead networks, the long-term operational benefits including substantial reduction in fault frequency, improved supply continuity, and longer service life justify the investment. Underground cable networks are thus confirmed as an effective solution for enhancing power distribution quality and reliability, particularly in urban areas with high fault incidence.